Integrating Human Capital Development with Financial Inclusion: Evidence from Remote Regions of Indonesia - Rizka Cintya Edwar; Yuni Riskita Mangopo (Journal of International Conference Proceedings, 2025)
Human capital development plays an essential role in promoting inclusive and sustainable economic systems, particularly in the digital era where competitiveness is increasingly driven by knowledge, skills, and innovation. Nevertheless, remote communities often face challenges such as limited access to education, financial services, and entrepreneurial opportunities, which restrict their integration into broader economic structures. This study examines the relationship between human capital development and financial inclusion, highlighting the mediating influence of the entrepreneurial mindset. The research targeted Papuan students at Universitas Cenderawasih who had completed entrepreneurship courses and gained hands-on learning experiences through activities such as entrepreneurship bazaars. Out of a total population of 220 students, 142 participants were chosen based on Slovin’s sampling formula. A quantitative approach was applied, collecting data through structured questionnaires and analyzing them with SmartPLS to explore both direct and indirect effects. The findings indicate that human capital development substantially enhances financial inclusion, while entrepreneurial mindset strengthens this relationship by acting as a mediator. These results highlight the critical need to integrate human capital development with financial inclusion initiatives to empower academic communities in remote areas. Moreover, the study provides practical recommendations for policymakers, educators, and financial institutions to formulate inclusive strategies tailored for emerging economies. Keywords: Human Capital Development; Financial Inclusion; Entrepreneurial Mindset; Remote Regions; Sustainable Development.